Algae as hosts for epifaunal bryozoans: Role of functional groups and taxonomic relatedness - Liuzzi, Maria Gabriela (2011)
Macroalgae build biogenic habitats which give shelter and provide a suitable physical environment for a great variety of organisms. Structural complexity of algal substrates may influence the composition of their attached epifauna. The aim of this study is to test whether the taxonomic relatedness of the algal hosts and the functional groups to which they belong influence the species richness and composition of their epifaunal bryozoans. We analysed 36 algal genera from the Atlantic coast of South America between 42°S and Cape Horn. Changes in bryozoan species richness (number of species) among different algal functional groups (filamentous algae, foliose algae, corticated foliose algae, corticated macrophytes) were non-significant. The composition of the epifaunal assemblages differed significantly only between filamentous and foliose algae. Sheet-like bryozoans (i.e. encrusting, pluriserial colonies) were more frequent on foliose than on filamentous algae, while runner-like species (i.e. uniserial stolons) were characteristic epibionts on filamentous thallii. Similarity of bryozoan assemblages increased with increasing taxonomic relatedness of their hosts. As most filamentous seaweeds analysed in this study are members of the Order Ceramiales, the influence of algal taxonomic relatedness and functional groups on the composition of their bryozoan assemblages can be viewed as two different aspects of the same phenomenon.